An evaluation of the adequacy of the retirement benefits and the social security schemes in Zimbabwe: Case of Midlands Province - Makombe, Prince (Midlands State University, 2020)
The importance of social security benefits comes from the ability of the benefit to be able to satisfy the needs and demand of the beneficiaries by the time they are going to receive their benefits. Social security systems have been under challenges and that the labour organization systems are too expensive harm to the socio-economic well-being of employees. It is observed that retirement time kills more than hard work period ever does. It has been a common burden to family members to take care of their retirees since they are old enough to work. The small income the retirees get from their pensions are affected by the change of cost of living due to cost of production, famine, drought among others that bring unexpected prevailing prices of goods and services. Due to the demand of the people on adequate social services, this study aimed at examining the adequacy of the retirement benefits and the social security schemes in Zimbabwe. Interviews, questionnaires and literature reviews have led to confirmation that social security institutions are characterized by lots of inefficiencies. In terms of benefits administration, there is a very low coverage, inadequate benefits which are not indexed to get rid of the ill effects of inflation, poor involvement of members in decision making, low levels of compliance and high administrative costs in relation to contributions income. Furthermore, customer satisfaction cannot even be predicted as a result of poor quality services. Consequently, one would conclude that the social security institutions in Zimbabwe do not provide the benefits that have a required meaning to the members. Stratified sampling data collection method such as observations and questionnaire were the tools used in the study. There is a need to enforce Laws in Zimbabwe so that registered employers and members will be heavily penalized if they fail to submit contributions into schemes they are registered; and there is a need for the Social Security Institution in Zimbabwe to increase their membership size by extending their coverage into the informal sector where there is large segment of working population.